New Nipponentomon species from northern Asia (Protura: Acerentomata, Nipponentomidae) - Bu, Yun; Wu, Dong Hui; Shrubovych, Julia; Yin, Wenying (Zootaxa, 2013)
Nipponentomon imadatei sp. nov. from Northeast China and Nipponentomon taiga sp. nov. from Siberia, Russia are de-scribed. Nipponentomon heterothrixi Yin & Xie is redescribed based on type materials and lectotype and paralectotypes are designed for the species. Nipponentomon bidentatum and N. nippon are reported for the first time from China. Nippo-nentomon imadatei sp. nov. is characterized by a short labrum, absence of seta P1a on tergite VII and presence of three A-setae on sternites IV–VI. It is similar to N. jaceki from the Russian Far East, but differs in the shape of the comb, shape of seta β1 on the foretarsus, length of sensillum e on the foretarsus, and in chaetotaxy on tergite I and sternites IV–VI. Nipponentomon taiga sp. nov. is characterized by a short labrum, presence of seta P2a' on nota, seta P0a on tergite I, seta P1a on tergites I–VII, and absence of seta P3a on tergites II–VII. It is similar to N. heterothrixi, but differs in absence of seta d6 on the head, shape of accessory setae on tergites VI and VII, long and setiform seta β1, and shorter sensilla c, e, g, a' and c' on the foretarsus than in sensilla in N. heterothrixi and in the porotaxy. A key for the world species of the genus is provided and the porotaxy of five species is reported in detail.